Critical thinking in the classroom: the historical method and historical discourse as tools for teaching social studies - Burgos-Videla, Carmen; Parada-Ulloa, Marcos; Martínez-Díaz, Javiera (Frontiers in Sociology, 2025)
IntroductionThis article addresses the pressing need to transform the teaching of History and Social Sciences by moving beyond traditional approaches centered on rote memorization and content reproduction. Instead, it advocates for a pedagogy oriented toward the development of critical and reflective thinking, through the incorporation of the historical method and the construction of historical discourse as central pillars of the educational process. The ultimate aim is to strengthen civic education from a critical and contextually grounded perspective.MethodsThe study adopts a hermeneutic and critical-reflexive approach, based on an exhaustive review of national and international academic literature. The hermeneutic circle is employed as a methodological strategy to analyze how pedagogical practices can reinterpret historical sources, challenge dominant narratives, and foster historical dialogue in the classroom.ResultsThe research identifies various pedagogical strategies that operationalize the proposed approach, including structured historical debates, school-based research projects, collaborative analysis of primary and secondary sources, and the integrated use of digital technologies. These strategies are articulated with key categories of historical thinking: contextualization, causality, multicausality, continuity, and change. The study also emphasizes the importance of critical source comparison and the integration of multiple perspectives.Discussion and conclusionThe findings suggest that adopting a socio-critical approach to the teaching of History can transform the classroom into a space for active reflection, fostering a critical and socially engaged citizenry. The study underscores the need to promote teacher training processes that integrate these methodologies, as well as to encourage future empirical research to assess their impact in diverse educational settings. In sum, it advocates for a historical education that forms critically aware individuals, capable of interpreting the past and acting ethically in the present.